2005
DOI: 10.1200/jco.2005.11.094
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Cisplatin Plus Methotrexate Versus Methotrexate, Vinblastine, Epirubicin, and Cisplatin in Locally Advanced Bladder Cancer: Results of a Randomized, Multicenter, Phase III Trial (AUO-AB 05/95)

Abstract: CM cannot be considered inferior to M-VEC with regard to progression-free survival of patients with locally advanced bladder cancer after radical cystectomy. Moreover, patients receiving adjuvant CM combination therapy experienced significantly less grade 3 and 4 leukopenia than patients treated with M-VEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 28 publications
0
43
0
2
Order By: Relevance
“…This relatively small benefit raises the question of whether chemotherapy is best reserved for the adjuvant setting, given selectively to high-risk patients. Unfortunately, the evidence for a survival benefit from adjuvant chemotherapy has been less convincing, and trials addressing this issue have had significant design flaws [90][91][92][93][94][95]. Two recent metaanalyses concluded that adjuvant therapy has a modest, statistically significant improvement in survival over surgery alone [96,97].…”
Section: Neoadjuvant and Adjuvant Chemotherapymentioning
confidence: 99%
“…This relatively small benefit raises the question of whether chemotherapy is best reserved for the adjuvant setting, given selectively to high-risk patients. Unfortunately, the evidence for a survival benefit from adjuvant chemotherapy has been less convincing, and trials addressing this issue have had significant design flaws [90][91][92][93][94][95]. Two recent metaanalyses concluded that adjuvant therapy has a modest, statistically significant improvement in survival over surgery alone [96,97].…”
Section: Neoadjuvant and Adjuvant Chemotherapymentioning
confidence: 99%
“…Decreased toxicity coupled with a similar response rate to MVAC appears to strengthen the role of gemcitabine and cisplatin in the treatment of locally advanced bladder cancer. Lehmann et al [68] recently compared adjuvant cisplatin and methotrexate versus methotrexate, vinblastine, epirubicin, and cisplatin (MVEC) in a randomized phase III trial in patients with locally advanced bladder cancer [68]. Overall 5-year progression-free survival rates were similar for cisplatin and methotrexate and MVEC at 46.3 AE 4.6% versus 48.8 AE 4.5%, respectively.…”
Section: Neoadjuvant and Adjuvant Chemotherapymentioning
confidence: 97%
“…Radical cystectomy is recommended as curative treatment for locally advanced bladder cancer including tumor stages pT3 and pT4a and/or involvement of regional lymph nodes [3]. With increasing T stage, and in particular, for the patients with clinically extravesical cancer, the situation is much worse: the overall 5-year survival ranging from 60 to 75% for pT2 tumors to 4-35% for pT3, pT4 or node-positive (N?)…”
mentioning
confidence: 99%